Pan‐cancer multi‐omics analyses reveal crosstalk between the Hippo and immune signaling pathways in the tumor microenvironment. Issue 4 (27th December 2021) - Wang, Chengyu; Zhu, Tong; Zhao, Zhangxiang; Chen, Bo; Chen, Tingting; Dong, Qi; Liu, Mingyue; Zhuang, Shuping; Yang, Fan; Liu, Yaoyao; Yang, Min; Gu, Yunyan; et al.
Abstract : The Hippo signaling pathway is critical for carcinogenesis. However, the roles of the Hippo signaling pathway in the tumor immune microenvironment have been rarely investigated. This study systematically analyzed the relationship between the Hippo signaling pathway and immune cell infiltration across 32 cancer types. Both bioinformatics analyses and biological experiments revealed that the downstream effector of Hippo signaling YAP1 might inhibit CD8+ T cell infiltration by upregulating the expression of the transcription factor CREB1 in uterine corpus endometrial carcinoma. In addition, esophageal carcinoma (ESCA) patients were classified into three subtypes based on the Hippo–immune gene panel. The subtypes of ESCA had distinct characteristics in immune cell infiltration, immune pathways, and prognosis. Thus, this study also reveals a new classification of the immune subtypes with prognostic characteristics in ESCA. Abstract : The present study systematically analyzed the relationship between the Hippo signaling pathway and immune cell infiltration using multi‐omics data across 32 cancer types. The findings revealed the mutual effect of the downstream effector of Hippo signaling YAP1 and the transcription factor CREB1 in uterine corpus endometrial carcinoma. The Hippo–immune network was also used to reveal new subtypes in esophageal carcinoma.